Inundation requirements for persistence and recovery of river red gums (Eucalyptus camaldulensis) in semi-arid Australia. (April 2015) - Catelotti, K.; Kingsford, R.T.; Bino, G.; Bacon, P.
Abstract: Increasing water abstraction is severely degrading the world's wetlands, which is frequently reflected in the condition of flood dependent organisms. Understanding minimum requirements under which thresholds are crossed from desired to undesired states can improve managing for resilience and avoid catastrophic ecological consequences. The Macquarie Marshes, a Ramsar-listed wetland in eastern Australia is located in a catchment with a long history of water resource development. It is also a catchment in which there has been a strong focus on wetland recovery using environmental flows. We investigated changes in the condition of 212 river red gum trees ( Eucalyptus camaldulensis ), a long-lived flood dependent species, at 17 sites, over 18 years (1993–2011). Four variables were measured for each tree: crown density, crown size, dead branches and epicormic growth. More than half (56.13%, 119) of the healthy trees first measured in 1993, showed no signs of life by 2011. Using historic inundation mapping, we identified that condition declined with reduced flooding. The probability of inundation in the previous five years had the strongest explanatory power, with strong increasing threshold responses of persistence and recovery associated with probabilities of flooding exceeding 5 years in the previous 10 years. We extended our modelling to the river red gum forests of the Macquarie Marshes floodplain, showing that 37% of the area had a predicted survival probability lower than P  = 0.6 while similar probabilities were present in only 12% of the area within the Macquarie Marshes Nature Reserve. The condition of river red gum forests, using the relationships identified, provide a useful measure of ecosystem health, particularly if extended to understanding of reproduction, germination and recruitment in relation to different scenarios for environmental flows. Embedding such a monitoring strategy in an adaptive management framework provides considerable promise for ongoing learning and improvement of management, not just for river red gums but also other indicators. There is a possibility that the current poor ecological condition of the Macquarie Marshes can be redressed with increased environmental flows restoring some of the river red gum forests that are a key characteristic of the wetland.